Exploring education an introduction to the foundations of education - Sadovnik, Alan R.; Cookson, Peter W. Jr.; Semel, Susan F.; Coughlan, Ryan W. (New York Routledge, 2018)
This much-anticipated fifth edition of Exploring Education offers an alternative to traditional foundations texts by combining a point-of-view analysis with primary source readings. Pre- and in-service teachers will find a solid introduction to the foundations disciplines -- history, philosophy, politics, and sociology of education -- and their application to educational issues, including school organization and teaching, curriculum and pedagogic practices, education and inequality, and school reform and improvement. This edition features substantive updates, including additions to the discussion of neo-liberal educational policy, recent debates about teacher diversity, updated data and research, and new selections of historical and contemporary readings. At a time when foundations of education are marginalized in many teacher education programs and teacher education reform pushes scripted approaches to curriculum and instruction, Exploring Education helps teachers to think critically about the "what" and "why" behind the most pressing issues in contemporary education. -- Provided by publisher.
"Fourth edition published by Routledge 2013"--T.p. verso.
Includes bibliographical references (pages 531-578) and index.
Keywords: Education -- United States; Educational sociology -- United States; Education -- United States -- Philosophy